2020
DOI: 10.1109/access.2020.3002569
|View full text |Cite
|
Sign up to set email alerts
|

Constraining State Variables and Control Signal via Sliding Mode Control Approach

Abstract: In this paper the issue of constraining the control input and the state variables in continuoustime systems via sliding mode control was considered. The sliding mode controller was designed using the reaching law technique. Further, the time-varying convergence rate was selected so that the fastest, finitetime, monotonic convergence of the state to the predefined sliding hyperplane simultaneously satisfying both control input and state limitations is ensured. Sufficient condition that guarantees these properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, in this paper we examine this issue upon the perturbed continuous time system with time-varying model uncertainties and external disturbances (which do not need to satisfy the matching conditions). We propose a reaching law that ensures the fastest, monotonic and finite-time convergence of the representative point to the predefined switching hyperplane, simultaneously limiting state constraints and control input, extending results obtained in [37]. The novelty of this paper consists of considering the state constraints in the forms of linear combinations, fully eliminating the chattering effect on the boundaries of the admissible set and increasing the convergence speed by taking into account maximal impact of model uncertainties at every time instant.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, in this paper we examine this issue upon the perturbed continuous time system with time-varying model uncertainties and external disturbances (which do not need to satisfy the matching conditions). We propose a reaching law that ensures the fastest, monotonic and finite-time convergence of the representative point to the predefined switching hyperplane, simultaneously limiting state constraints and control input, extending results obtained in [37]. The novelty of this paper consists of considering the state constraints in the forms of linear combinations, fully eliminating the chattering effect on the boundaries of the admissible set and increasing the convergence speed by taking into account maximal impact of model uncertainties at every time instant.…”
Section: Introductionmentioning
confidence: 79%
“…Theorem 5. If the control strategy for plant (2) is defined by (13) with sliding hyperplane selected according to (16), then system output rate of change is bounded in the following way for all k ≥ n…”
Section: Proposed Sliding Hyperplanementioning
confidence: 99%
“…It has been demonstrated that, if the sliding variable rate of change is bounded, then the output rate of change will also be proportionally limited. Furthermore, its bound strictly depends on coefficient 𝜆 from sliding hyperplane (16) and parameter 𝜀 from reaching law (8). Consequently, any constraints (4) placed on the system can be satisfied with the proper choice of these parameters.…”
Section: Proposed Sliding Hyperplanementioning
confidence: 99%
See 2 more Smart Citations